Diabetes and Onset of Natural Menopause. Issue 8 (August 2015) - Brand, J. S.; Onland-Moret, N. C.; Eijkemans, M. J. C.; Tjønneland, A.; Roswall, N.; Overvad, K.; Fagherazzi, G.; Clavel-Chapelon, F.; Dossus, L.; Lukanova, A.; Grote, V.; Bergmann, M. M.; et al.
<x xml:space="preserve">Abstract</x> ABSTRACT The age at natural menopause (ANM) in the Western world ranges from 40 to 60 years, with an average onset of 51 years. The exact mechanisms underlying the timing of ANM are not completely understood. Both genetic and environmental factors are involved. The best-established environmental factor affecting ANM is smoking; menopause occurs 1 to 2 years earlier in smokers. In addition to genetic and environmental factors, chronic metabolic diseases may influence ANM. Some evidence suggests that diabetes may accelerate menopausal onset. With more women of childbearing age receiving a diagnosis of diabetes, it is important to examine the impact of diabetes on reproductive health. This study was designed to determine whether ANM occurs at an earlier age among women who have diabetes before menopause than in women without diabetes. Data were obtained from the European Prospective Investigation into Cancer and Nutrition (EPIC) study, a large multicenter prospective cohort study investigating the relationship between diet, lifestyle, and genetic factors and the incidence of cancer and other chronic diseases. A cohort of 519, 978 men and women, mostly aged 27 to 70 years, were recruited primarily from the general population between 1992 and 2000. A total of 367, 331 women participated in the EPIC study. After exclusions, 258, 898 of these women met study inclusion criteria. Diabetes status at baseline and menopausal age were based on self-report and were obtained through questionnaires. Participants were asked if they had ever been diagnosed with diabetes and if so at what age. Associations of diabetes and age at diabetes diagnosis with ANM were estimated using time-dependent Cox regression analyses, with stratification by center and adjustments for age, smoking, reproductive, and known diabetes risk factors including smoking and with age from birth to menopause or censoring as the underlying time scale. Overall, there was no statistically significant lower risk of becoming menopausal among women with diabetes than women with no diabetes; the hazard ratio (HR) was 0.94, with a 95% confidence interval (CI) of 0.89 to 1.01. However, compared with women with no diabetes, women with diabetes before the age of 20 years had an earlier menopause (10–20 years [HR, 1.43; 95% CI, 1.02–2.01] and <10 years [HR, 1.59; 95% CI, 1.03–2.43]), whereas women with diabetes at age 50 years or older had a later menopause (HR, 0.81; 95% CI, 0.70–0.95). No association with ANM was found for diabetes onset between the ages 20 and 50 years. Strengths of the study include its large sample size and the measurement of a broad set of potential confounders. However, there were several limitations. First, results may have been underestimated because of survival bias. Second, the sequence of menopause and diabetes in women with a late age at diabetes is uncertain, as both events occur in a short period, and both diabetes and menopause status were based on self-report, not verified by medical records. Third, no distinction was made between types 1 and 2 diabetes. Although there is no overall association between diabetes and age at menopause, the data suggest that early-onset diabetes may accelerate menopause. The delaying effect of late-onset diabetes on ANM is not in agreement with other studies suggesting the opposite association.